Correlations between Left Ventricular and Left Atrial Function Assessed by Speckle Tracking Echocardiography in Patients with Treated Well-Controlled Arterial Hypertension - Beata Uziębło-Życzkowska; Paweł Krzesiński (Cardiology Research and Practice)
Introduction. Even in patients with well-controlled arterial hypertension (AH) and without significant comorbidities, left ventricular (LV) and left atrial (LA) strain abnormalities may sometimes be found in speckle-tracking echocardiography. Therefore, the aim of this study was to investigate the correlation between LA strain and LV diastolic and systolic function in a group of patients with treated, well-controlled AH. Material and methods. LA contractile, conduit, and reservoir function, together with echocardiographic signs of LV diastolic function and LV global longitudinal strain (LV GLS), were assessed in 101 patients with treated, well-controlled AH who met the standard criteria of normal LV ejection fraction (LVEF) and normal LV diastolic function. Results. A relevant percentage of study participants presented lower than reference LV (−18.7% for LV GLS) and LA strain (32.9% for LAS during reservoir phase, LASr; −15.9% for LAS during contraction phase, LASct; and −13.9% for LAS during conduit phase, LAScd) values. Moreover, there were statistically significant differences in LA longitudinal strain (LAS) values (LASr (31.43 vs. 36.33; p = 0.0007) and LAS LAScd (−13.09 vs. −15.79; p = 0.008)) between patients with high (>the absolute value of −20%) and lower (≤the absolute value of −20%) LV GLS, confirmed by significant correlations between LASr, LAScd, and GLS. In the correlations analysis between LAS values and LV diastolic function parameters, statistical significance was obtained for the following: LASct (contraction) versus e’avg, LASct versus E/A, LASct versus A, LAScd versus e’avg, LAScd versus E/A, and LAScd versus A. Conclusions. LV and LA strain abnormalities occurred within a significant percentage of patients with treated, well-controlled AH. Impaired LA strain is associated with lower LV strain and reduced LV diastolic function parameters, reflecting both the passive and active properties of the LA.